Explaining political disagreement - Mason, Andrew 1959- (Cambridge University Press, 1993)
This book considers a variety of explanations of why political disagreement is so extensive and persistent. The author examines variants of the 'contestability' and 'imperfection' conceptions which have dominated political theory: the idea that political disagreement is so pervasive because of its value-ladenness; that key political concepts are essentially contested; that those who occupy very different political positions fail to understand each other. He argues that we need to develop a framework which borrows elements from both schools of thought, presupposing some form of moral cognitivism, while recognizing that many political disputes cannot be resolved to the satisfaction of every reasonable person. Within such a framework he shows how empirical models can be constructed which give an active role not only to the agent's reasons for his or her beliefs, but also to other psychological and sociological considerations
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Philosophie; Politische Wissenschaft; Consensus (Social sciences); Political science / Philosophy; Konsens; Politische Theorie; Hochschulschrift